Immigrants’ use of emergency primary health care in Norway: a registry-based observational study - Sandvik Hogne (BMC Health Services Research, 2012)
Abstract Background Emigrants are often a selected sample and in good health, but migration can have deleterious effects on health. Many immigrant groups report poor health and increased use of health services, and it is often claimed that they tend to use emergency primary health care (EPHC) services for non-urgent purposes. The aim of the present study was to analyse immigrants’ use of EPHC, and to analyse variations according to country of origin, reason for immigration, and length of stay in Norway. Methods We conducted a registry based study of all immigrants to Norway, and a subsample of immigrants from Poland, Germany, Iraq and Somalia, and compared them with native Norwegians. The material comprised all electronic compensation claims for EPHC in Norway during 2008. We calculated total contact rates, contact rates for selected diagnostic groups and for services given during consultations. Adjustments for a series of socio-demographic and socio-economic variables were done by multiple logistic regression analyses. Results Immigrants as a whole had a lower contact rate than native Norwegians (23.7% versus 27.4%). Total contact rates for Polish and German immigrants (mostly work immigrants) were 11.9% and 7.0%, but for Somalis and Iraqis (mostly asylum seekers) 31.8% and 33.6%. Half of all contacts for Somalis and Iraqis were for non-specific pain, and they had relatively more of their contacts during night than other groups. Immigrants’ rates of psychiatric diagnoses were low, but increased with length of stay in Norway. Work immigrants suffered less from respiratory and gastrointestinal infections, but had more injuries and higher need for sickness certification. All immigrant groups, except Germans, were more often given a sickness certificate than native Norwegians. Use of interpreter was reduced with increasing length of stay. All immigrant groups had an increased need for long consultations, while laboratory tests were most often used for Somalis and Iraqis. Conclusions Immigrants use EPHC services less than native Norwegians, but there are large variations among immigrant groups. Work immigrants from Germany and Poland use EPHC considerably less, while asylum seekers from Somalia and Iraq use these services more than native Norwegians.